The Edinburgh companion to gothic and the arts - Punter, David (Edinburgh companions to literature and the humanities., 2019)
The Gothic is a contested and complicated phenomenon, extending over many centuries and across all the arts. In The Edinburgh Companion to the Gothic and the Arts, the range of essays run from medieval architecture and design to contemporary gaming and internet fiction; from classical painting to the modern novel; from ballet and dance to contemporary Goth music. The contributors include many of the best-known critics of the Gothic (e.g., Hogle, Punter, Spooner, Bruhm) as well as newer names such as Kirk and Round. The editor has put all these contributors in touch with each other in the preparation of their essays in order to ensure the maximum benefit to the reader by producing a well-integrated book which will prove much more than a collection of disparate essays, but rather a distinctive contribution to a field.